Partial Replacement of Kosaric Medium With Banana Leaf Ash Extract for the Culture of Spirulina Platensis (Annals of Bangladesh Agriculture, 2023)
The use of banana leaf ash extract (BLAE) as a replacement of Kosaric medium (KM) to grow spirulina (Spirulina platensis) was investigated. KM was partially replaced with more affordable and locally available BLAE at 0, 10, 30, 50, and 70% concentrations. The spirulina was grown for 18 days at room temperature in the experimental media with artificial lighting and aeration. By replacing KM with BLAE, the 30% replacement produced the highest biomass of S. platensis. It was observed that replacing of KM by 30% with BLAE produced biomass of 1.22 g/L, which was similar to that of 1.33 g/L with control (P